Estimation of the collection grain sorghum samples for breeding of new varieties - V. V. Kovtunov; N. N. Sukhenko; О. А. Lushpina; Yu. V. Repeshko (Зерновое хозяйство России)
Sorghum has valuable biological features and great potential for use. Grain sorghum is characterized with super adaptability, good resistance to air and soil droughts and high temperatures, therefore it can become one of the promising crops in crop rotations. The developed varieties should be early-maturing and large-kernelled. The current paper has presented the study results of the collection nursery of grain sorghum samples of the world breeding. The trials were carried out in the laboratory for grain sorghum breeding and seed production of the FSBSI “Agricultural Research Center “Donskoy” in 2019–2021. According to the study results, there was established that, depending on the year, early-maturing forms made up 39.6–74.4 % of the studied collection. The samples ‘No.2-13’, ‘D577/19’, ‘F7 Pioner 88 x 412 Feterita rannyaya’ and the varieties ‘Kinelskoe 63’, ‘Kamyshinskoe 64’, ‘Kamyshinskoe 75’ were characterized by a short vegetation period (up to 90 days). In 2021, there were 44.8 % of the collection samples with ‘number of kernels per panicle’ from 1001 to 1500 pcs. When compared with the standard variety ‘Zernogradskoe 88’ (1532 pcs.), there were identified eight samples exceeding it in ‘kernel percentage per panicle’. There was found out that the largest part of the collection samples was characterized by a mean and large ‘1000-kernel weight’ (64.1–72.4 % and 16.8–25.5 %, respectively). A very large ‘1000-kernel weight’ (>40 g) through three years was established for the samples ‘Avans’, ‘Atlant’, ‘No.61–13’, ‘Spur Feterita’, ‘Redhull Feterita’, ‘Feterita’. There have been selected the forms with a complex of valuable traits for their further use in breeding work. The purpose of the current study was to research the collection material of various breeding according to such traits as ‘number of kernels per panicle’, ‘1000-kernel weight’, ‘length of a vegetation period’, which have a greater effect on grain sorghum productivity and to identify valuable sources due to these traits.